Macrophage-derived neutrophil chemotactic factor is involved in the neutrophil recruitment inhibitory activity present in the supernatants of LPS-stimulated macrophages - B. M. Tavares-Murta; F. Q. Cunha; M. Dias-Baruffi; M. C. Roque-Barreira; S. H. Ferreira (Mediators of Inflammation)
In a previous study, we demonstrated the presence of a neutrophil recruitment inhibitory factor (NRIF) in the supernatants of LPS-stimulated macrophages. Recently, the purification of a 54 kDa protein, identified as the macrophage-derived neutrophil chemotactic factor (MNCF) was reported. Since NRIF and MNCF are obtained under the same conditions, and, since the intravenous administration of TNF-α and IL-8 inhibits neutrophil migration, we have investigated whether MNCF could be responsible for this inhibitory activity. After affinity chromatography of the macrophage supernatants on a D-galactose column, the inhibitory activity was recovered in both the unbound (D-gal−) and bound (D-gal+) fractions, with MNCF being found in the D-gal+ fraction. Further gel filtration of the latter on Superdex 75 yielded a single peak containing both activities. In a cytotoxicity assay, most of the TNF found in the crude supernatants was recovered in the D-gal− fraction. Furthermore, the incubation of the D-gal− fraction with anti-TNF-α plus anti-IL-8 antisera partially prevents its inhibitory effect on neutrophil migration, but had no effect on the D-gal+ activity. Overall, these results suggest that the D-gal− inhibitory effect is partially mediated by TNF-α and IL-8, and that MNCF accounts for the inhibition of neutrophil migration in vivo by the D-gal+ fraction.